(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article describes globalization, its essence, spiritual threats that are increasing in the process of globalization and effective ways to fight against them, the content and scope of reforms implemented in various fields in our country in this regard. Also, relevant recommendations and conclusions are given on this topic.